2001
DOI: 10.1155/edr.2001.201
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived Neurotrophic Factor Regulates Energy Expenditure Through the Central NervousSystem in Obese Diabetic Mice

Abstract: It has been previously demonstrated that brain-derived neurotrophic factor (BDNF) regulates glucose metabolism and energy expenditure in rodent diabetic models such as C57BL/KsJ-leprdb/leprdb (db/db) mice. Central administration of BDNF has been found to reduce blood glucose in db/db mice, suggesting that BDNF acts through the central nervous system. In the present study we have expanded these investigations to explore the effect of central administration of BDNF on energy metabolism. Intracerebroventricular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 30 publications
4
83
0
1
Order By: Relevance
“…In particular, the hypothalamus is a primary site of convergence and integration for redundant energy status signaling, which includes central and peripheral neural inputs, as well as hormonal and nutritional factors (23 -25). Nonomura et al reported that intracerebroventricular injection of BDNF increases hepatic insulin sensitivity and pancreatic insulin content (12). These results suggest that BDNF in the central nervous system is an important regulator of glucose metabolism in peripheral organs via "inter-tissue communication", and the hypothalamus is an essential brain region that directs this system (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the hypothalamus is a primary site of convergence and integration for redundant energy status signaling, which includes central and peripheral neural inputs, as well as hormonal and nutritional factors (23 -25). Nonomura et al reported that intracerebroventricular injection of BDNF increases hepatic insulin sensitivity and pancreatic insulin content (12). These results suggest that BDNF in the central nervous system is an important regulator of glucose metabolism in peripheral organs via "inter-tissue communication", and the hypothalamus is an essential brain region that directs this system (24).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, some reports have suggested that BDNF regulates glucose metabolism by improving insulin sensitivity and increasing pancreatic insulin production (11,12). In addition, it has been reported that BDNF enhances hepatic InsR signaling in streptozotocin-induced diabetic mice (13).…”
Section: Introductionmentioning
confidence: 99%
“…Impairments in BDNF synthesis or production in animals are associated with increased food intake, reduced energy expenditure, and weight gain (Kernie et al, 2000;Lyons et al, 1999;Nakagawa et al, 2000;Nonomura et al, 2001;Ono et al, 1997;Rios et al, 2001;Tsuchida et al, 2001). In contrast, central infusions of BDNF in rats lead to severe, dose-dependent appetite suppression, weight loss, and increase in serotonin (Pelleymounter et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…For example, BDNF heterozygous mice and mice in which the BDNF gene has been deleted in the brain's excitatory neurons are obese (Kernie et al, 2000;Lyons et al, 1999;Rios et al, 2001). Both central and peripheral administration of BDNF decreases food intake, increases energy expenditure, ameliorates hyperinsulinemia, and hyperglycemia, and reduces weight in diabetic db/db mice (Nakagawa et al, 2000;Nonomura et al, 2001;Ono et al, 1997;Tsuchida et al, 2001). Interestingly, a recent study demonstrated a strong association of the Val66Met BDNF variant with a number of eating disorders (Ribases et al, 2003(Ribases et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Subcutaneous administration of BDNF when started early (4 weeks) was able to prevent the agerelated increases in blood glucose levels seen in db=db mice (179). Others have shown that intracerebroventricular administration of BDNF can lower glucose levels and increase insulin concentrations in the pancreas in db=db mice, suggesting the CNS had a role in glucose metabolism (128). CR in db=db mice increases hippocampal BDNF levels and is associated with increased dendritic spine density (153).…”
Section: Molecular Mechanisms Of Adaptive Responses To Oxidative Stressmentioning
confidence: 99%